Efficacy of a Second-Grade Science Program: Increasing Science Outcomes for All Students. - Doabler, Christian T.; Therrien, William J.; Longhi, Maria A.; Roberts, Greg; Hess, Katherine E.; Maddox, Steven A.; Uy, Jasmine; Lovette, Gail E.; Fall, Anna-Maria; Kimmel, Georgia L.; Benson, Sarah; VanUitert, Victoria J.; et al. (Remedial & Special Education, 2021)
This study, which was reviewed through the Registered Report process, examined the initial efficacy of the Scientific Explorers program (Sci2) on second-grade students' science achievement. Sci2 is grounded in the growing body of empirical research on science instruction, embedding principles of explicit instruction within a guided inquiry-based design framework. Eighteen second-grade classrooms were randomly assigned to treatment or control conditions. A cluster randomized controlled trial was employed, with 294 students nested within classrooms and classrooms nested within condition. The Sci2 program was implemented for a total of 10 lessons (5 hr) in treatment classrooms, whereas control classrooms provided business-as-usual science instruction. Overall treatment effects were observed on three of four science outcome measures. The reported effects were moderate to large, with effect sizes (Hedges' g) ranging from 0.48 to 0.94. Moderation analyses indicated that science knowledge at pretest did not moderate Sci2's effects. Implications for practice and research are discussed.